RANCANGAN SISTEM INFORMASI PEMBELIAN BARANG DENGAN METODOLOGI BERORIENTASI OBYEK - Mujito, Mujito; Asmanto, Budi (Universitas Muhammadiyah Metro, 2023)
In companies / agencies need an information system for purchasing goods so that it can be done computerized and not done using Microsoft Office. Purchasing goods is an overall process used to hold something necessary in meeting the needs of goods in the company. The need for goods is very important in supporting the work process in a company / agency, the unavailability of goods can hamper performance. Supervision of requests is generally less than optimal, because many procurement request files are still stored in the File and sometimes some are torn and lost, so a system is needed that handles the request process. The process of making requests for goods in the procurement section has difficulty updating the availability of goods so that it hampers the process of demand for goods, so a module is made to be able to monitor the process of demand for goods and activities related to the purchase of goods. So that the procurement department can speed up the process of disbursing data, minimizing errors and data loss. The system that is created later uses a Visual .Net programming language with a MySQL database, all processes will be stored into the MySQL database.